Diaspory skandynawskie i transetniczne przestrzenie społeczne Wikingów - Stanisławski, Błażej (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2019)
Migrations of the Norsemen, which took place in the early Middle Ages, led to an emergence of new social formations, operating also outside Scandinavia, including “Polish” territories. These formations can be defined as diasporas or transethnic social spaces as part of the transmigration and transnational paradigms, developed with respect to sociology.